2012
DOI: 10.4021/wjon531w
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-Cell Lymphoma at the Site of a Herpes Zoster Scar

Abstract: Herpes zoster, also known as shingles, occurs upon reactivation of a primary infection with varicella zoster virus (VZV). Risk factors for reactivation include stress, older age, and immunosuppression, all of which are associated with a decrease in host immunity. Common complications of herpes zoster include scarring and post-herpetic neuralgia (PHN). Cutaneous lesions such as granuloma annulare, lymphomas, and sarcoid granulomas have also been reported to potentially arise at the site of herpes zoster. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Multiple cutaneous malignancies have been reported within areas of prior herpes zoster, including squamous cell carcinoma, angiosarcoma, Kaposi sarcoma, CTCL, and cutaneous B-cell lymphoma. 6 , 7 , 8 , 9 , 10 Zosteriform MF is an exceedingly rare variant of MF characterized by lesions that occur in a dermatomal distribution. 11 In 1991, Williams et al 12 described a case in which several firm nodules in a zosteriform distribution over the left neck and shoulder were found to be MF on biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cutaneous malignancies have been reported within areas of prior herpes zoster, including squamous cell carcinoma, angiosarcoma, Kaposi sarcoma, CTCL, and cutaneous B-cell lymphoma. 6 , 7 , 8 , 9 , 10 Zosteriform MF is an exceedingly rare variant of MF characterized by lesions that occur in a dermatomal distribution. 11 In 1991, Williams et al 12 described a case in which several firm nodules in a zosteriform distribution over the left neck and shoulder were found to be MF on biopsy.…”
Section: Discussionmentioning
confidence: 99%
“… 3 In addition to mimicking neoplasms, cutaneous VZV may serve as the initial locale of hematologic malignancies. 4 As VZV may demonstrate either histopathologic mimicry or Wolf's isotopic response, a complete workup may include bone marrow analysis.…”
Section: Discussionmentioning
confidence: 99%
“…VZV infections have been reported to cause not only transient pancytopenia but also aplastic anemia that may require allogeneic HSCT [66,227,[235][236][237]. Several studies have shown that HZ is associated with increased risk of developing solid tumors as well as lymphoid malignancies [238][239][240][241][242].…”
Section: Vzv-associated Pancytopenia and Aplastic Anemiamentioning
confidence: 99%